2011
DOI: 10.1111/j.1471-4159.2011.07186.x
|View full text |Cite
|
Sign up to set email alerts
|

The cannabinoid type‐1 receptor carboxyl‐terminus, more than just a tail

Abstract: J. Neurochem. (2011) 117, 1–18. Abstract The cannabinoid type‐1 (CB1) receptor is a G protein‐coupled receptor that binds the main active ingredient of marijuana, Δ9‐tetrahydrocannabinol, and has been implicated in several disease states, including drug addiction, anxiety, depression, obesity, and chronic pain. In the two decades since the discovery of CB1, studies at the molecular level have centered on the transmembrane core. This interest has now expanded as we discover that other regions of CB1, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 155 publications
(405 reference statements)
2
25
0
Order By: Relevance
“…Similar findings have been described for the human cannabinoid receptor 1 (27,55,56). Using overexpression, purification, and circular dichroism spectroscopy analysis of the fulllength CB1 C terminus as well as different substitution variants, it was demonstrated that it is the level of hydrophobicity rather than specific amino acids that is critical for helix formation and, thus, targeting to the PM of this GPCR (27,55,56). Another example that hydrophobic amino acid residues in the membrane-proximal C terminus allowing ␣-helix formation are essential for ER exit and PM localization has been described for the human vasopressin II receptor (28).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings have been described for the human cannabinoid receptor 1 (27,55,56). Using overexpression, purification, and circular dichroism spectroscopy analysis of the fulllength CB1 C terminus as well as different substitution variants, it was demonstrated that it is the level of hydrophobicity rather than specific amino acids that is critical for helix formation and, thus, targeting to the PM of this GPCR (27,55,56). Another example that hydrophobic amino acid residues in the membrane-proximal C terminus allowing ␣-helix formation are essential for ER exit and PM localization has been described for the human vasopressin II receptor (28).…”
Section: Discussionsupporting
confidence: 84%
“…Taken together our results suggest that the FX 6 LL motif itself has an important role for ␣-helix formation but not as a sequence-specific sorting motif in the TGR5␤ 2 AR chimera. Similar findings have been described for the human cannabinoid receptor 1 (27,55,56). Using overexpression, purification, and circular dichroism spectroscopy analysis of the fulllength CB1 C terminus as well as different substitution variants, it was demonstrated that it is the level of hydrophobicity rather than specific amino acids that is critical for helix formation and, thus, targeting to the PM of this GPCR (27,55,56).…”
Section: Discussionsupporting
confidence: 73%
“…1F). Cumulating evidence from transfection experiments on cell lines suggests a major role of the C-terminus of the CB 1 R in heterologous desensitization and G-protein uncoupling (Daigle et al, 2008a,b;Ellis et al, 2006;Stadel et al, 2011). Furthermore, Ellis et al (2006) suggest a novel pharmacological paradigm, whereby ligands modulate the function of receptors for which they have no significant inherent affinity by acting as regulators of receptor heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…This has been particularly studied in the context of chronic cannabinoid consumption to decipher the mechanisms of addiction. Mechanisms of desensitization and downregulation are not totally elucidated but they probably involve phosphorylation of the receptor and transcription of immediate early genes [112,113]. Interestingly, CB1 receptors do not desensitize at the same rate, depending on the brain structure [113].…”
Section: Impact Of Dietary ω-6/ω3 Pufas On Proteins Of the Endocannabmentioning
confidence: 99%